A Finance Handbook in a Suitcase Part I: A Comparison of Teaching and Learning Experiences in Different Countries. (13th July 2020) - Nicolini, Gianni
Abstract : This article summarizes several teaching experiences that the author, an Italian professor of finance, has had in different countries. In addition, it compares the functioning of different academic environments. The aim is to help scholars who are beginning their academic careers with techniques to take into account the cultural and behavioral differences in different academic environments and countries. Also, the article could help: (i) students who want to study abroad to smooth their transition into a new and different academic system, and (ii) visiting professors that will be teaching abroad for the first time.